Production of Enriched Biomass by Carotenogenic Yeasts Cultivated on by-Products of Poultry Processing-A Screening Study - Holub, Jiří; Szotkowski, Martin; Chujanov, Oleg; Špačková, Dominika; Sniegoňová, Pavlína; Márová, Ivana (Microorganisms, 2023)
Carotenogenic yeasts are a group of microorganisms producing valuable metabolites such as carotenoids, ergosterol, ubiquinone or fatty acids. Their exceptional adaptability allows them to grow in diverse conditions. Owing to their extracellular lipase activity, they are capable of processing many lipid-type waste substrates. This study discusses the processing of poultry waste, specifically fat and feathers by using carotenogenic yeasts. Poultry fat does not require any pre-treatment to be utilized by yeast, but hydrolytic pre-treatment is required for the utilization of the nitrogen contained in feathers. Glycerol was used as a supplementary substrate to support the culture in the early stages of growth. Seven yeast strains were used for the experiments, of which the strain Rhodotorula mucilaginosa CCY19-4-25 achieved exceptional results of biomass production: 29.5 g/L on poultry fat + 10% glycerol at C/N ratio 25 and 28.3 g/L on media containing poultry fat + 25% glycerol at C/N 50. The bioreactor cultivation of the Rhodosporidium toruloides strain in media containing glycerol and feather hydrolysate as a nitrogen substrate achieved a biomass yield of 34.92 g/L after 144 h of cultivation. The produced enriched yeast biomass can be used as a component for poultry feeding; thus, the study is performed under the biorefinery concept.
Keywords: poultry waste fat; poultry feather; carotenoids; lipids; biorefinery; enriched biomass; carotenogenic yeasts